Numerical modelling of the impact of coronavirus disease 2019 on fertility and population growth rate in Malaysia - shehab Abdulhabib Alzaeemi; Saratha Sathasivam; Kim Gaik Tay; Nur Hafieza Adzhar; Nur Hannani Shamsudin; Nur Ain Izzati Ramli (Institute of Advanced Engineering and Science, 2024)
Over the past four years, the world has grappled with an unprecedented global pandemic caused by COVID-19, resulting in a significant surge in reported cases and fatalities across numerous countries. This health crisis has had far-reaching demographic repercussions, with a notable decline in global birth rates, plummeting by 1.12% in 2020 compared to the preceding year. This trend is exemplified in Malaysia, where the number of births dwindled from 123,751 in September 2019 to 116,434 during the corresponding period in 2020. The reluctance to have children stems from the heightened vulnerability to the virus, compounded by financial constraints due to widespread unemployment, further dampening population growth. This study is dedicated to comprehending the impact of COVID-19 on Malaysia's population growth rates and forecasting its trajectory for the subsequent five years following the outbreak. Researchers scrutinized the data using numerical methods and population modeling and employed the Euler method, aided by MATLAB software, to compare their findings against authentic population figures. Their analysis disclosed that the COVID-19 pandemic affected Malaysia's population growth rates, although it did not directly impact mortality rates, as recovery rates exceeded mortality rates. In essence, the pandemic has primarily influenced birth rates, contributing to a noteworthy demographic shift in the country.